2006
DOI: 10.4141/s06-031
|View full text |Cite
|
Sign up to set email alerts
|

Windrow temperatures and chemical properties during active and passive aeration composting of beef cattle feedlot manure

Abstract: Pre-vs. post-turning sampling of the active treatment was also compared. Mean daily temperature was warmest at the bottom windrow location (53.6ºC) and coolest at the top (46.4ºC) in the active treatment, but warmest at the top (44.1ºC) and coolest at the bottom (33.9ºC) in the passive treatment. Final compost from the passive treatment had significantly higher total N (TN), total C (TC), electrical conductivity (EC), Na, and Cl than the active treatment. There were no significant treatment effects on C:N rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…The slurry treatment had an increasing C:N ratio over the first 5 weeks after which it stabilized, while the solid manure storage treatment had a decline in the C:N ratio over time. A decline in C: N ratio during the composting of cattle manure has also been observed in other studies (e.g., Larney and Olsen, 2006;Larney et al, 2008).…”
Section: And N Dynamics During Manure Storagesupporting
confidence: 83%
See 2 more Smart Citations
“…The slurry treatment had an increasing C:N ratio over the first 5 weeks after which it stabilized, while the solid manure storage treatment had a decline in the C:N ratio over time. A decline in C: N ratio during the composting of cattle manure has also been observed in other studies (e.g., Larney and Olsen, 2006;Larney et al, 2008).…”
Section: And N Dynamics During Manure Storagesupporting
confidence: 83%
“…Literature values of C losses during storage of solid cattle manure in static piles range from 13 to 47%, with C losses increasing with storage length (Petersen et al, 1998;Larney and Olsen, 2006;Luebbe et al, 2011). The values from the present study fall within this range and are similar to the longer term storage losses of 47% seen in studies with manure stored for 6 months.…”
Section: And N Dynamics During Manure Storagesupporting
confidence: 81%
See 1 more Smart Citation
“…Larney and Olson (2006) found that composting resulted in increased concentrations of soluble Na and K.…”
Section: Resultsmentioning
confidence: 99%
“…Composting decreases manure volume (Larney et al 2000), and eliminates pathogenic bacteria , human parasites (Van Herk et al 2004) and weed seed viability (Larney and Blackshaw 2003). Despite its benefits, like most manure-handling or storage practices, composting is associated with N and C losses (Larney et al 2006a(Larney et al , 2008Larney and Olson 2006). Most N is volatilized as NH 3 , but some is emitted as N 2 O, a greenhouse gas, while C losses as greenhouse gases (CO 2 , CH 4 ) also occur (Hao et al 2001(Hao et al , 2004.…”
mentioning
confidence: 99%